Classical bovine spongiform encephalopathy and chronic wasting disease: two sides of the prion coin - Nicholas J. Haley; Juergen A. Richt (Animal Diseases, 2023)
Abstract Transmissible spongiform encephalopathies (TSEs) are a group of progressive and ultimately fatal neurologic diseases of man and animals, all resulting from the propagated misfolding of the host’s normal cellular prion protein. These diseases can be spontaneous, heritable, anthropogenic/iatrogenic, or in some cases horizontally transmissible, and include such notable TSEs as bovine spongiform encephalopathy (BSE) of cattle and chronic wasting disease (CWD) of cervids. Although they are both unequivocally protein misfolding disorders, they differ markedly in their pathogenesis, transmissibility, and zoonotic potential. While the BSE epidemic has largely abated over the past three decades following global feed bans on ruminant meat and bone meal, CWD, which is readily transmitted through various forms of excreta, has rapidly expanded from its original endemic zone to encompass much of North America, along with recently identified foci in Scandinavia. Most importantly, although the classical form of BSE has proven transmissible to humans consuming contaminated beef or beef products, so far there have been no conclusive reports on the zoonotic transmission of CWD to humans. The underlying basis for these differences – whether host or agent directed – are not well understood, though may be due to inherent differences in the three-dimensional structure of the misfolded BSE or CWD prion proteins or the expression levels and tissue distribution of respective cellular prion proteins. With the uncontrolled geographic spread of CWD, it is imperative that we improve our understanding of the factors governing prion disease pathogenesis, transmission, and zoonotic potential.